To solve this equation, we can start by isolating the variable x.
First, let's distribute the 5/3 to the x:
3 - (5/3)x = 18
Next, let's get rid of the constant term 3 by subtracting 3 from both sides:
- (5/3)x = 18 - 3
This simplifies to:
- (5/3)x = 15
To get rid of the fraction, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(- (5/3)x) * (3/5) = 15 * (3/5)
This gives us:
-x = 9
Finally, to solve for x, we can multiply both sides by -1:
(-1)(-x) = (-1)(9)
This yields:
x = -9
Therefore, the solution to the equation is x = -9.
3 - 5/3x = 18
1 answer